A randomised controlled trial of a digital learning game in the context of a design-based research project. (2016) - Freeman, Barbara; Higgins, Kristina
This paper reports the findings of a randomised control trial of The Mars Game, an immersive 3D digital learning game designed to teach mathematics and programming to students in secondary schools. The study demonstrated that The Mars Game treatment group's engagement with learning was significantly greater than the control group. It also showed significantly greater learning outcomes, with the increase coming mainly from programming. This study was preceded by four studies, conducted over two years, as part of a design-based research project. Through reflection on the broader project, we observe how key events influenced our design decisions, and how these decisions impacted the intricate yet inextricable relationship between students' active engagement and their achievement. We explore why this connection is critical to improving learning.